2021
DOI: 10.1186/s12890-021-01727-9
|View full text |Cite
|
Sign up to set email alerts
|

Impact of high-flow oxygen therapy during exercise in idiopathic pulmonary fibrosis: a pilot crossover clinical trial

Abstract: Background Supplemental oxygen delivered with standard oxygen therapy (SOT) improves exercise capacity in patients with idiopathic pulmonary fibrosis (IPF). Although high-flow nasal cannula oxygen therapy (HFNC) improves oxygenation in other respiratory diseases, its impact on exercise performance has never been evaluated in IPF patients. We hypothesized that HFNC may improve exercise capacity in IPF subjects compared to SOT. Methods This was a pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Most studies on exercise in patients with ILD compared the effects of HFNC therapy with those of standard‐ or Venturi‐mask oxygen therapy 11–14 . However, these studies did not clarify the effects of oxygen and gas flow rates on exercise tolerance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies on exercise in patients with ILD compared the effects of HFNC therapy with those of standard‐ or Venturi‐mask oxygen therapy 11–14 . However, these studies did not clarify the effects of oxygen and gas flow rates on exercise tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, HFNC therapy improved endurance time, minimum percutaneous oxygen saturation (SpO 2 ), and leg effort at iso‐time in patients with stable idiopathic pulmonary fibrosis (IPF). Subsequent reports confirmed that HFNC therapy prolongs endurance time 12–14 …”
Section: Introductionmentioning
confidence: 94%
“…Three-day survival and in-hospital mortality did not differ significantly between the groups ( 39 ). Furthermore, HFNC compared to standard oxygen therapy seems to improve endurance time of IPF patients during constant-load exercise testing on cycloergometer in laboratory studies ( 40 42 ).…”
Section: Breathlessness—pathophysiology and Treatmentmentioning
confidence: 99%
“…In this study, HFNC oxygen therapy significantly improved endurance time compared to controls (647.5 vs. 577 s, p = 0.0018). Previously, Badenes-Bonet et al 4 enrolled 10 IPF patients with more severe disease (FVC 58% predicted, DL CO 31% predicted, minimum oxygen saturation [SpO 2 ] % during 6-min walking test [6MWT] 76%) using a variable fraction of inspired oxygen (FiO 2 ) and HFNC setting. Endurance time during cardiopulmonary exercise testing (CPET) was significantly greater using HFNC compared to Venturi mask (VM) oxygen therapy (494 vs. 381 s, p = 0.01).…”
Section: To the Editorsmentioning
confidence: 99%